(untitled) (International Journal of Functional Research in Science and Engineering (IJFRSE), 2026)
Virtual laboratories and system modeling brings revolutionary opportunities to the modern educational process to improve student engagement, strengthen conceptual understanding, and close access inequality in science education. This paper examines the effectiveness of these technologies in facilitating active learning, critical thinking, and development of practical skills in the various learning contexts. The study relies on peer-reviewed articles, school reports, and case studies of 1980-2025 to discuss their applications, results, and issues using a secondary data synthesis approach. Results show that virtual labs and simulations enhance student learning by 15-30 percent in STEM fields and also overcome inequity in limited resources settings. Training gaps, technological infrastructure, and inclusive design are also found with suggestions to implement it in a scalable manner and provide access fairly. The synthesis of the evidence presented worldwide suggests that this work can offer practical information to teachers and policymakers to adopt technology to create active and inclusive learning experiences.